2007
DOI: 10.1088/0957-4484/19/01/015301
|View full text |Cite
|
Sign up to set email alerts
|

Directed self-assembly of quantum structures by nanomechanical stamping using probe tips

Abstract: We demonstrate that nanomechanically stamped substrates can be used as templates to pattern and direct the self-assembly of epitaxial quantum structures such as quantum dots. Diamond probe tips are used to indent or stamp the surface of GaAs(100) to create nanoscale volumes of dislocation-mediated deformation, which alter the growth surface strain. These strained sites act to bias nucleation, hence allowing for selective growth of InAs quantum dots. Patterns of quantum dots are observed to form above the under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
26
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
(47 reference statements)
2
26
0
2
Order By: Relevance
“…The positioning of QDs can be achieved by modification of the GaAs surface in the nanoscale. Electron beam lithography (EBL) [4-6,14], local oxidation [15-17], focused ion beam [18], or nanomechanical stamping [19] can be used to fabricate small holes on the substrate surface. The deformation of surface chemical potential leads to accumulation of In adatoms in the holes which then act as preferential nucleation sites for InAs QDs.…”
Section: Introductionmentioning
confidence: 99%
“…The positioning of QDs can be achieved by modification of the GaAs surface in the nanoscale. Electron beam lithography (EBL) [4-6,14], local oxidation [15-17], focused ion beam [18], or nanomechanical stamping [19] can be used to fabricate small holes on the substrate surface. The deformation of surface chemical potential leads to accumulation of In adatoms in the holes which then act as preferential nucleation sites for InAs QDs.…”
Section: Introductionmentioning
confidence: 99%
“…Surface patterns involving the introduction of dislocations by nanoindentation, using standard and atomic force microscopy (AFM) techniques, have been used in order to determine the nucleation site of quantum dots and nanocrystals. [7][8][9][10] It is therefore important to investigate the details of the early stages of nanoscale mechanical deformation in cubic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…22 The introduction of dislocations has been used to modulate strain in GaAs for site selective nucleation of InAs crystallites. 23 Scratching is another method to introduce dislocations in semiconductor crystals. It has been recently shown that scratching of InP can produce highly localized distributions of dislocations along the scratch line.…”
Section: Introductionmentioning
confidence: 99%